Intravenous therapy duration and outcomes in melioidosis: a new treatment paradigm. - Matthew C Pitman; Tara Luck; Catherine S Marshall; Nicholas M Anstey; Linda Ward; Bart J Currie (Public Library of Science (PLoS), 2015)
BACKGROUND:International melioidosis treatment guidelines recommend a minimum 10 to 14 days' intravenous antibiotic therapy (intensive phase), followed by 3 to 6 months' oral therapy (eradication phase). This approach is associated with rates of relapse, defined as recurrence following the eradication phase, that can exceed 5%. Rates of recrudescence, defined as recurrence during the eradication phase, have not previously been reported. In response to low eradication phase completion rates in Australia, a local guideline has evolved over the last ten years recommending a longer minimum intensive phase duration for many cases of melioidosis. METHODOLOGY/ PRINCIPAL FINDINGS:This retrospective cohort study reviews antibiotic duration for the first episode of care for all patients diagnosed with melioidosis and surviving the intensive phase during a recent three year period in the tropical north of Australia's Northern Territory; we also review adherence to the current local guideline and treatment outcomes. Of 215 first episodes of melioidosis surviving the intensive phase, the median (interquartile range) intensive phase duration was 26 (14-34) days. One hundred and eight (50.2%) patients completed eradication therapy; 58 (27.0%) patients took no eradication therapy. At 28 months' follow-up, one (0.5%) relapse and eleven (5.1%) recrudescences had occurred. On exact logistic regression analysis, the only independent risk factors for recrudescence were self-discharge during the intensive phase (odds ratio 6.2 [95% confidence interval 1.2-30.0]) and septic shock (odds ratio 5.3 [95% confidence interval 1.1-25.7]). CONCLUSIONS/ SIGNIFICANCE:Relapsed melioidosis is rare in patients who receive a minimum intensive phase duration specified by our guideline and extended according to clinical progress. Recrudescence rates may improve with reductions in rates of self-discharge. Given the low relapse rate despite a high rate of eradication therapy non-adherence, the duration and necessity of eradication therapy for different patients after guideline-concordant intensive therapy should be evaluated further.